A light and electron microscope study of the structure and regulatory peptide production of the islets of Langerhans in the normal baboon pancreas - Wolfe-Coote, S. A.(Sonia Ann) (Stellenbosch : Stellenbosch University, 2012)
Thesis (D.Sc.) -- University of Stellenbosch, 1985.